A Rare Case of Exophiala Dermatitidis Isolation in a Patient with Non-Cystic Fibrosis Bronchiectasis: Colonization or True Infection? - Francesco Rocco Bertuccio; Nicola Baio; Simone Montini; Valentina Ferroni; Vittorio Chino; Lucrezia Pisanu; Marianna Russo; Ilaria Giana; Elisabetta Gallo; Lorenzo Arlando; Klodjana Mucaj; Mitela Tafa; et al. (Diagnostics)
Background: Exophiala dermatitidis is a dematiaceous, thermotolerant, yeast-like fungus increasingly recognized as an opportunistic pathogen in chronic airway diseases. While commonly associated with cystic fibrosis, its clinical significance in non-cystic fibrosis bronchiectasis (NCFB) remains unclear. Case Presentation: We report the case of a 66-year-old immunocompetent woman with a history of breast cancer in remission and NCFB, who presented with chronic cough and dyspnea. Chest CT revealed bilateral bronchiectasis with new pseudonodular opacities. Bronchoalveolar lavage cultures identified E. dermatitidis, along with Pseudomonas aeruginosa and methicillin-sensitive Staphylococcus aureus. Given clinical stability and the absence of systemic signs, initial therapy included oral voriconazole, levofloxacin, doxycycline, and inhaled amikacin. Despite persistent fungal isolation on repeat bronchoscopy, the patient remained asymptomatic with stable radiologic and functional findings. Antifungal therapy was discontinued, and the patient continued under close monitoring. The patient exhibited clinical and radiological stability despite repeated fungal isolation, reinforcing the hypothesis of persistent colonization rather than active infection. Discussion: This case underscores the diagnostic challenges in distinguishing fungal colonization from true infection in structurally abnormal lungs. In NCFB, disrupted mucociliary clearance and microbial dysbiosis may facilitate fungal persistence, even in the absence of overt immunosuppression. The detection of E. dermatitidis should prompt a comprehensive evaluation, integrating clinical, radiologic, and microbiologic data to guide management. Voriconazole is currently the antifungal agent of choice, though therapeutic thresholds and duration remain undefined. Conclusions: This report highlights the potential role of E. dermatitidis as an under-recognized respiratory pathogen in NCFB and the importance of a multidisciplinary, individualized approach to diagnosis and treatment. This case underscores the need for further research on fungal colonization in NCFB and the development of evidence-based treatment guidelines. Further studies are needed to clarify the pathogenic significance, optimal management, and long-term outcomes of E. dermatitidis in non-CF chronic lung diseases.